Study of pitting corrosion behaviour of stainless and duplex stainless steels - Tan, Wilfred Liang Wei. (2011)
Pitting corrosion usually occurs on materials in corrosive chlorine containing environment. Pitting corrosion test methodology is described in ASTM G48 Method A and materials are commonly qualified for sub-sea application (chlorine containing atmosphere) following ASTM G48, method A experiment at a particular temperature. This project aims to give reader a better understanding on pitting corrosion mechanism of stainless steels and duplex stainless steels, factors affecting pitting corrosion mechanism, effect of temperature on pitting corrosion mechanism its impact to oil and gas industry. This report also introduces other testing methods that are available in the industry to meet its needs. Pitting corrosion tests were conducted on three different grades of stainless steel at different temperatures. Results showed the 904L grade stainless steels exhibited better pitting corrosion property as compared to 316L and 307. The results of this studies gives useful comparison of the pitting corrosion properties of these steels as function of test temperature. To compare pitting resistance behavior of stainless with super duplex steels, the author has conducted pitting corrosion test on a 25%Cr super duplex steels and compared the weight loss values to that of the austenitic stainless steels at same temperature. As expected super duplex steels showed much better corrosion properties as compared stainless steels. The author also proposes future research using different methods and testing parameters.